Psychoreligious Therapy to Reduce Stress Levels for Inmates in Narcotics Prison Samarinda: Terapi Psikoreligious untuk menurunkan tingkat stress untuk Narapidana di Lapas Narkotika Samarinda - Fuad Fansuri; Putri Ameda; Amelia Salsabila; Rabi’atil Husni; Khusnul Khatimah (Journal of Empowerment and Community Service (JECSR), 2023)
This study aims to evaluate the effectiveness of psychoreligious therapy in reducing the level of stress among inmates at the Narcotics Prison in Samarinda. This therapy combines psychological approaches with spiritual or religious elements to facilitate the healing process. An experimental research method with a pre-test post-test control group design was used, involving inmates as research subjects. The results show that psychoreligious therapy significantly reduces the level of stress among inmates, as evidenced by lower stress scores in the intervention group compared to the control group. The clinical implications of this research highlight the importance of integrating spiritual aspects in efforts to rehabilitate inmates to reduce stress and improve their well-being.